Evaluación de la extracción de azúcares presentes en la pulpa de café residual para la obtención de bioproductos (2021)
Coffee occupies the second place as the most important basic product in the world, which represents large productions in coffee-growing countries, therefore, its industry generates high amounts of waste that become a source of contamination for the natural resources present in the coffee zone. The main residue of coffee growing is coffee pulp, which if used could provide added value, due to its contents of pectin, cellulose, hemicellulose, polyphenols, caffeine, proteins, tannins, among other substances that can be used in the production of bioproducts in different industries. The objective of this research was to evaluate the extraction of sugars present in the residual coffee pulp to obtain bioproducts, for its development a chemical characterization of the residual coffee pulp was carried out through a bibliographic review in which the results obtained by different authors were compare, followed by evaluating the techniques for obtaining sugars using a selection matrix with the most relevant parameters, finally, according to the selected techniques, some studies based on obtaining bio-products from hydrolyzed residual coffee pulp were reported.